Attendance and diagnostic yield of repeated two-sample faecal immunochemical test screening for colorectal cancer. Issue 1 (14th September 2015) - Kapidzic, Atija; van Roon, Aafke H C; van Leerdam, Monique E; van Vuuren, Anneke J; van Ballegooijen, Marjolein; Lansdorp-Vogelaar, Iris; Spijker, Wolfert; Izelaar, Kirsten; Hol, Lieke; Kuipers, Ernst J
Abstract : Objective: Limited data exist on attendance and additional yield of 2-sample faecal immunochemical testing (FIT) screening during multiple rounds. We therefore conducted a population-based colorectal cancer screening trial comparing attendance and yield of repeated 1-sample and 2-sample FIT screenings. Design: Two randomly selected groups of average-risk subjects aged 50–74 years were invited for two rounds of either 1-sample (n=5007) or 2-sample (n=3197) FIT (OC-sensor Micro) screening. The test was considered positive if at least one sample was positive (cut-off 50 ng/mL; 10 µg haemoglobin/g). Results: The cumulative attendance rate was similar for repeated 1-sample and 2-sample FIT screenings (1-sample FIT: 68.1%; 2-sample FIT: 67.1%, p=0.368). The positivity rate in the second round was lower for 1-sample FIT (6.2%, 95% CI 5.4% to 7.2%) than for 2-sample FIT (8.4%, 95% CI 7.1% to 9.8%, p=0.007), whereas the detection rate of advanced neoplasia (AN, 1-sample FIT: 1.9%, 95% CI 1.2% to 2.2%; 2-sample FIT: 1.7%, 95% CI 1.2% to 2.5%, p=0.861) and the positive predictive value (1-sample FIT: 32%, 95% CI 24% to 40%; 2-sample FIT: 21%, 95% CI 15% to 29%, p=0.075) did not differ. After two rounds of screening, the cumulative diagnostic yield of AN for 1-sample FIT was 29.3 per 1000 invitees, compared with 34.0 for 2-sample FIT (p=0.241). Conclusions: Using 2-sample FIT instead of 1-sample FIT does not result in a higher detection rate of AN in the second round of repeated FIT screening. Furthermore, both strategies lead to a similar yield of AN over two rounds. These findings imply that 1-sample FIT screening is preferred over 2-sample FIT screening.